Medium-chain fatty acids suppress lipotoxicity-induced hepatic fibrosis via the immunomodulating receptor GPR84 - Ryuji Ohue-Kitano; Hazuki Nonaka; Akari Nishida; Yuki Masujima; Daisuke Takahashi; Takako Ikeda; Akiharu Uwamizu; Miyako Tanaka; Motoyuki Kohjima; Miki Igarashi; Hironori Katoh; Tomohiro Tanaka; et al. (JCI Insight, 2023)
Medium-chain triglycerides (MCTs), which consist of medium-chain fatty acids (MCFAs), are unique forms of dietary fat with various health benefits. G protein–coupled 84 (GPR84) acts as a receptor for MCFAs (especially C10:0 and C12:0); however, GPR84 is still considered an orphan receptor, and the nutritional signaling of endogenous and dietary MCFAs via GPR84 remains unclear. Here, we showed that endogenous MCFA-mediated GPR84 signaling protected hepatic functions from diet-induced lipotoxicity. Under high-fat diet (HFD) conditions, GPR84-deficient mice exhibited nonalcoholic steatohepatitis (NASH) and the progression of hepatic fibrosis but not steatosis. With markedly increased hepatic MCFA levels under HFD, GPR84 suppressed lipotoxicity-induced macrophage overactivation. Thus, GPR84 is an immunomodulating receptor that suppresses excessive dietary fat intake–induced toxicity by sensing increases in MCFAs. Additionally, administering MCTs, MCFAs (C10:0 or C12:0, but not C8:0), or GPR84 agonists effectively improved NASH in mouse models. Therefore, exogenous GPR84 stimulation is a potential strategy for treating NASH.